2023
DOI: 10.1186/s12905-023-02265-8
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to increase the uptake of cervical cancer screening in low- and middle-income countries: a systematic review and meta-analysis

Abstract: Background To identify effective interventions to increase the uptake of cervical cancer screening (CCS) for low-and middle-income countries (LMICs). Methods We searched PubMed, CENTRAL, ISI Web of Sciences, Scopus, OVID (Medline), CINAHL, LILACS, CNKI and OpenGrey for randomized controlled trials (RCTs) and cluster RCTs conducted in LMICs from January 2000 to September 2021. Two reviewers independently screened studies, extracted data, assessed ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…The literature addresses effective ways to optimize cervical screening attendance in LMICs. In 24 studies (15 RCT and 9 cluster with RCTs including 1 study from Cameroon), self-sampling was superior to VIA (RR 1.93 95% CI 1.66–2.25); reminder phone calls or SMS texts facilitated attendance when compared to letter invitation (RR 1.72, 95%CI 1.27–2.32, RR 1.59, 95% CI 1.46–5.19); free or subsidized costs optimized attendance (RR 1.60, 95% CI 1.10–2.33); and community-based HPV testing was superior to hospital-collected HPV testing (RR 1.67, 95% CI 1.53–1.82) [ 15 ]. A recent sequential prospective study in the West Region of Cameroon showed that in the 10 months from September 2018–May 2019, there was a passive approach of community information channels with media announcements, posters in women’s associations, churches and integrated health centers [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The literature addresses effective ways to optimize cervical screening attendance in LMICs. In 24 studies (15 RCT and 9 cluster with RCTs including 1 study from Cameroon), self-sampling was superior to VIA (RR 1.93 95% CI 1.66–2.25); reminder phone calls or SMS texts facilitated attendance when compared to letter invitation (RR 1.72, 95%CI 1.27–2.32, RR 1.59, 95% CI 1.46–5.19); free or subsidized costs optimized attendance (RR 1.60, 95% CI 1.10–2.33); and community-based HPV testing was superior to hospital-collected HPV testing (RR 1.67, 95% CI 1.53–1.82) [ 15 ]. A recent sequential prospective study in the West Region of Cameroon showed that in the 10 months from September 2018–May 2019, there was a passive approach of community information channels with media announcements, posters in women’s associations, churches and integrated health centers [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Uterine cervical carcinoma (UCC) remains a major global health concern, accounting for significant morbidity and mortality in women worldwide. Despite considerable research efforts and advances in screening and prevention strategies, UCC continues to pose a substantial public health challenge, particularly in low- and middle-income countries ( Srinath et al, 2022 ; Ton et al, 2022 ; Dau et al, 2023 ; Tin et al, 2023 ). A comprehensive understanding of the etiological factors underlying the development of UCC is crucial for devising improved prevention, early detection, and treatment strategies.…”
Section: Introductionmentioning
confidence: 99%